Respiratory Chlamydia Infection Induce Release of Hepoxilin A3 and Histamine Production by Airway Neutrophils - Patel, Katir K.; Webley, Wilmore C. (Frontiers in Immunology, 2018)
Background: Hepoxilins are biologically active metabolites of arachidonic acid that are formed through the 12-lipoxygenase pathway. Hepoxilin A3 is now known to be an important regulator of mucosal inflammation in response to infection by bacterial pathogens and was recently identified as a potent neutrophil chemoattractant in the intestinal mucosa. Our goal in this study was to determine if airway infection with Chlamydia in a murine model of allergic airway disease (AAD) induces hepoxilin secretion along with airway neutrophilia. Methods: We utilized an AAD adult Balb/c mouse model to evaluate airway pathology and immune response by assaying bronchoalveolar lavage (BAL) fluid cytokine, cellularity, histidine decarboxylase (HDC) as well as histamine released in response to in-vivo chlamydial antigen stimulation of purified airway neutrophils. Hepoxilin A3 production was determined by Western blot identification of 12-lipoxygenase precursor (12-LO). Results: Chlamydial infection induced increased production of IL-2, IL-12, TNF-α, and IFN-γ in BAL fluid compared to uninfected animals. Chlamydia-infected mice responded with robust airway neutrophil infiltration and upon induction of AAD increased their production of IL-4, IL-5 and IL-13 by >3 fold compared to unsensitized groups. In addition, 12-LO mRNA was upregulated in infected, but not in uninfected AAD mice, suggesting the production of hepoxilin A3. mRNA expression of HDC was induced only in neutrophils from the airways of Chlamydia-infected mice, but was not seen in AAD only or uninfected controls. When purified neutrophils from infected animals were challenged with chlamydial antigen in vitro there was significant histamine release. Conclusions: Our data confirms the production and release of hepoxilin A3 in the murine airways concomitant with airway neutrophilia in response to chlamydial infection. We further confirmed that Chlamydia provokes the production and release of histamine by these neutrophils. These findings suggest that neutrophils, provoked by Chlamydia infection can synthesize and release histamine, thereby contributing directly to airway inflammation.